2021
DOI: 10.17161/kjm.vol1414568
|View full text |Cite
|
Sign up to set email alerts
|

Time and Financial Costs for Students Participating in the National Residency Matching Program (the Match©): 2015 to 2020

Abstract: Purpose The purpose of this study was to provide information to assist students, faculty, and staff in making critical career-determining decisions regarding the residency NRMP “Match©” process. Method A 47-item survey questionnaire was developed and piloted on a regional campus in 2015. The questionnaire also incorporated a request for comments about the interviewing experience and suggestions to improve the process. The questionnaire was distributed each year in late February to early March… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 53 publications
4
13
0
Order By: Relevance
“…[31][32][33][34][35]37 Since the 2015-2016 application cycle, we have used an annual survey to track expenses, time spent interviewing, and other aspects of participation in the residency application process as reported by graduates of the University of Kansas School of Medicine (KUSM). 6,9,16 These surveys have very high response rates (range of 66.8%-97.0%, see Table 1), and the results are consistent with those of other studies. 6,9,16 For KUSM students, the average annual cost of applying to residency per applicant has been around $4,000, with the cost for applicants to individual specialties ranging from around $2,500 for family medicine to more than $8,000 for specialties such as radiation oncology and plastic surgery.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…[31][32][33][34][35]37 Since the 2015-2016 application cycle, we have used an annual survey to track expenses, time spent interviewing, and other aspects of participation in the residency application process as reported by graduates of the University of Kansas School of Medicine (KUSM). 6,9,16 These surveys have very high response rates (range of 66.8%-97.0%, see Table 1), and the results are consistent with those of other studies. 6,9,16 For KUSM students, the average annual cost of applying to residency per applicant has been around $4,000, with the cost for applicants to individual specialties ranging from around $2,500 for family medicine to more than $8,000 for specialties such as radiation oncology and plastic surgery.…”
Section: Discussionsupporting
confidence: 88%
“…Our students also have reported greater average time spent interviewing than those in other studies (25 to 30 days vs 25 days) but showed similar patterns by specialty and in the wide range reported by individual applicants. 6 We repeated this annual survey during the 2020-2021 residency application cycle to capture differences between this unique year and earlier patterns. Our hypotheses were that all applicants would report statistically significant lower costs and less time investment than those in previous years and that these reductions would be greater for applicants to non-primary care specialties.…”
Section: Discussionmentioning
confidence: 99%
“…We examined data from a six-year study (2016-2021) of interviewing time and expenses for students at our institution that has been reported in previous publications. 6,15,23 The participants were all fourthyear medical students who participated in the NRMP © to secure first-year residency positions. Each year, approximately 120 students from the main campus and 75 from the regional campus apply nationwide to residencies in the full spectrum of medical specialties.…”
Section: Methodsmentioning
confidence: 99%
“…[5][6][7] Travel accounted for 60% to 70% of all expenses with other costs predominantly for food and accommodation. 6,8 None of the over 20 studies of NRMP © applicant expenses have reported data for regional campus students, [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] but studies have commented on higher costs for "out of town" applicants and increased travel burden for those from non-metropolitan areas. 21,22 One large study attributed lower costs for students from the Northeastern region to the concentration of medical schools and residency programs in a single 500 mile area.…”
Section: Introductionmentioning
confidence: 99%
“…Interview-related travel expenses make up a large part of these costs. 18 Given this, several studies have been conducted to investigate potential cost saving alternatives to the traditional residency interview process prior to the COVID-19 pandemic which found that utilizing video interviews for residency and fellowship programs could be a cost-saving alternative. 5,1922 The 2020-2021 application cycle confirmed this.…”
Section: Introductionmentioning
confidence: 99%